GRAHA PERNIKAHAN DI YOGYAKARTA DENGAN PENEKANAN FLEKSIBILITAS ARSITEKTUR - Adinda Rafika Dani; Dwi Hedi Herianto; Musyawaroh Musyawaroh (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Wedding Center is a place that consist a wedding services equipment and a wedding celebration facility that informs the product development of the marriage market to the general public. Aims to provide the latest information on clients and the general public who interest in matters relating to marriage and provide office space facility as a representation of many companies engaged in the field of services and management of weddings. The design concept of the building is an implementation the formation of a flexible space where provide a possibility to use a room for an assortment of characters and events and the changing to the amount of space according to the user’s need might be done without changing the structure and shape of the building. Start from Wedding Center functions that provide wedding celebration, the most important thing is the wedding activities based on the wedding characters used, wedding time and the number of invited guests who will be invited to the wedding celebration . Therefore , by using the flexibility of architecture emphasis, then the layout changing and changing of the amount of space problems can be solved by upholding the value of the marriage’s sanctity. Keywords: Wedding Center, Flexibility of Architecture